Kedudukan Suami dan Istri dalam Hukum Perkawinan di Dunia Islam - Panjaitan, Fatimah; Ananda, Faisar; Al Faqih, Irwansyah (VISA: Journal of Vision and Ideas, 2025)
In the Discussion of the Position of Husband and Wife in Islamic Marriage Law, which is based on the Qur'an and Hadith, it continues to develop following social and cultural changes. Modern challenges such as gender equality and child protection encourage the need for this legal reform. Several Muslim countries, including Indonesia, have carried out reforms to adapt to the needs of the times. This study uses a qualitative approach with a literature study, reviewing secondary sources such as books, journal articles, and legal documents. The analysis was carried out descriptively-analytical and comparatively to compare the reform of marriage law in several Muslim countries. The results of the study show that the reform of marriage law in the Islamic world is the result of the interaction between tradition and modernity. Countries such as Tunisia, Morocco, and Indonesia have adopted reforms that are more in favor of women's and children's rights. Despite cultural barriers and conservatism, dialogue between scholars, government, and society is important to create relevant change.